Brood-guarding behaviour in Cory’s Shearwaters Calonectris diomedea - Catry, Paulo (2012)
Brood-guarding (or the continual attendance at the nest by one parent) has been relatively little studied in altricial birds. Parental investment in brood-guarding is often highly variable within a species, and the study of such variability may contribute to the understanding of the functions and regulation of this behaviour and of the tradeoffs involved in the choice between attending the nest and leaving to forage. In some colonial birds, it has been found that early nesting pairs attend their chick for longer than later nesting counterparts, giving rise to the synchronisation hypothesis that suggests that early pairs prolong broodguarding in order to reduce the probability of nest predation by a dilution effect. In this paper, for the first time we test the prediction that burrow-nesting colonial birds subject to little predation pressure should not display a seasonal decline in brood-guarding duration. The growth assistance hypothesis suggests that brood-guarding may allow the provision of frequent small meals and the efficient use of energy by chicks with poor homeothermic capabilities, resulting in improved early chick-growth. Finally, the chick-protection hypothesis predicts that chicks in more exposed nests should be brood-guarded for longer. Data collected at two Cory’s Shearwater Calonectris diomedea colonies situated in contrasting environments supported the synchronisation hypothesis, as there was no seasonal trend in brood-guarding duration. Contrary to the growth assistance hypothesis, chicks brood-guarded for longer periods did not have an improved growth (in one colony there was even a negative effect of brood-guarding on early chick development). Finally, we found no difference in brood-guarding between nests with contrasting levels of exposure to potential predators and weather. Despite confirming the prediction of the synchronisation hypothesis, more research is needed to identify the main factors underlying the variability of brood-guarding observed in this and other studies.